Potrayal of women in language - Santje Iroth; Muhammad Ilham Ali (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2026)
Language functions not only as a tool of communication but also as a means of constructing identity and reflecting cultural values, including gender roles. This study explores how the character Soe Dal Mi in the Korean drama Start-Up (2020) represents gender equality through language. The research questions examine how Soe Dal Mi’s language challenges patriarchal structures and what gender ideologies her discourse reveals. The objective is to analyze linguistic strategies that reflect resistance to traditional gender expectations in workplace contexts. Using Critical Discourse Analysis (CDA) by Fairclough (1992), this research analyzes Soe Dal Mi’s dialogues across three dimensions: text (lexical choices, grammar, language style), discourse practices (interactions and situational contexts), and social practices (gender ideologies and cultural norms). Data comprise dialogue excerpts from 16 episodes, collected through textual observation and script documentation. Findings reveal that Soe Dal Mi employs assertive language, direct communication, and professional terminology that challenge gender stereotypes, particularly in entrepreneurial settings. However, her discourse also demonstrates negotiation with traditional expectations through strategic code-switching. This study underscores media’s role in reshaping gender perceptions and contributes to discussions on gender representation in popular culture, with implications for understanding how Korean dramas influence Indonesian audiences’ views on women’s empowerment and workplace equality.